2018
DOI: 10.1051/0004-6361/201833725
|View full text |Cite
|
Sign up to set email alerts
|

A nearby super-luminous supernova with a long pre-maximum & “plateau” and strong C II features

Abstract: Context. Super-luminous supernovae (SLSNe) are rare events defined as being significantly more luminous than normal terminal stellar explosions. The source of the additional power needed to achieve such luminosities is still unclear. Discoveries in the local Universe (i.e. z < 0.1) are scarce, but afford dense multi-wavelength observations. Additional low-redshift objects are therefore extremely valuable. Aims. We present early-time observations of the type I SLSN ASASSN-18km/SN 2018bsz. These data are used to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 116 publications
2
33
0
Order By: Relevance
“…Anderson et al (2014b) performed this analysis on a large set of SNe II, and found a range of 56 Ni masses from 0.007 to 0.079 M , with a mean value of 0.033 M (σ = 0.024). A survey of literature values led to a mean mass 56 Ni = 0.044 M for a sample of 115 SNe II (Anderson 2019). Therefore, we conclude that the value retrieved for SN 2019hcc is within the expected range for a SN II.…”
Section: Ni Productionsupporting
confidence: 65%
See 1 more Smart Citation
“…Anderson et al (2014b) performed this analysis on a large set of SNe II, and found a range of 56 Ni masses from 0.007 to 0.079 M , with a mean value of 0.033 M (σ = 0.024). A survey of literature values led to a mean mass 56 Ni = 0.044 M for a sample of 115 SNe II (Anderson 2019). Therefore, we conclude that the value retrieved for SN 2019hcc is within the expected range for a SN II.…”
Section: Ni Productionsupporting
confidence: 65%
“…The features usually associated with O II are formed by many tens of overlapping lines (Anderson et al 2018b;Gal-Yam 2019), and can be contaminated by carbon and metal lines, and also by the presence of well-developed Balmer lines, all of which mean the features cannot be uniquely identified as O II. Therefore, whilst SN 2019hcc, SN 2014G, and SN 1998S could be valid candidates to show O II features as the Balmer lines are less prominent, SN 2013ej is less likely as it shows a strong H α profile suggesting the spectrum is dominated by H β at λ4861 and H γ at λ4340.…”
Section: T H E E a R Ly ' W ' S H A P E D F E At U R E : E L E M E N T S C O N T R I B U T I O N A N D T H E I R Nat U R Ementioning
confidence: 99%
“…In general, Type I SLSNe are noted for having low levels of polarization; however, SN 2015bn exhibited a significant rise in polarization after ∼ 20 d post-maximum (Leloudas et al 2017), with the evolution from the pre-maximum to post-maximum state clearly evident in spectropolarimetric observations (Inserra et al 2016). Our detection of significant polarization for SN 2018bsz also occurs ∼ 20 d (rest-frame) after the time of the V-band light-curve maximum (Anderson et al 2018a). Inserra et al (2016) and Leloudas et al (2017) both explained the behaviour of SN 2015bn as being due to a fundamental change in the asymmetry of the ejecta, with early-time emission arising from an almost spherical outer layer, whilst at later times the emission arise from a more aspherical interior (giving rise to the increase in polarization with time).…”
Section: Discussion and C O N C L U S I O N Smentioning
confidence: 50%
“…Discovered by ASAS-SN on 2018 May 17 (Stanek 2018), it was temporarily classified as a young Type II SN (Hiramatsu et al 2018a). It was later reclassified as a superluminous supernova (for a review see Gal-Yam 2019a), albeit a lower luminosity example (Anderson et al 2018a). Our observations commenced 4 d after the photometric light curve maximum or 69 d after the explosion date proposed by Anderson et al (2018a).…”
Section: Sn 2018bszmentioning
confidence: 99%
See 1 more Smart Citation